A Song of Ice and Fire: Cold and Hot Properties of Traditional Chinese Medicines - Liu, Juan; Feng, Wuwen; Peng, Cheng (Frontiers in Pharmacology, 2021)
The theory of cold and hot properties is the basic theory of traditional Chinese medicines (TCMs) and has been successfully applied to combat human diseases for thousands of years. Although the theory of cold and hot is very important to guide the clinical application of TCMs, this ancient theory remains an enigma for a long time. In recent years, more and more researchers have tried to uncover this ancient theory with the help of modern techniques, and the cold and hot properties of a myriad of TCMs have been studied. However, there is no review of cold and hot properties. In this review, we first briefly introduced the basic theories about cold and hot properties, including how to distinguish the cold and hot properties of TCMs and the classification and treatment of cold and hot syndromes. Then, focusing on the application of cold and hot properties, we take several important TCMs with cold or hot property as examples to summarize their traditional usage, phytochemistry, and pharmacology. In addition, the mechanisms of thermogenesis and antipyretic effect of these important TCMs, which are related to the cold and hot properties, were summarized. At the end of this review, the perspectives on research strategies and research directions of hot and cold properties were also offered.